Photophysiological responses of fragilariopsis cylindrus (bacillariophyceae) to nitrogen depletion at two temperatures - Petrou, K; Kranz, SA; Doblin, MA; Ralph, PJ (2012)
The photosynthetic efficiency and photoprotective capacity of the sea-ice diatom, Fragilariopsis cylindrus (Grunow) W. Krieg., grown in a matrix of nitrogen repletion and depletion at two different temperatures (-1°C and +6°C) was investigated. Temperature showed no significant effect on photosynthetic efficiency or photoprotection in F. cylindrus. Cultures under nitrogen depletion showed enhanced photoprotective capacity with an increase in nonphotochemical quenching (NPQ) when compared with nitrogen-replete cultures. This phenomenon was achieved at no apparent cost to the photosynthetic efficiency of PSII (F V/F M). Nitrogen depletion yielded a partially reduced electron transport chain in which maximum fluorescence (F M) could only be obtained by adding 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU). reoxidation curves showed the presence of Q B nonreducing PSII centers under nitrogen depletion. Fast induction curves (FICs) and electron transport rates (ETRs) revealed slowing of the electrons transferred from the primary (Q A) to the secondary (Q B) quinone electron acceptors of PSII. The data presented show that nitrogen depletion in F. cylindrus leads to the formation of Q B nonreducing PSII centers within the photosystem. On a physiological level, the formation of Q B nonreducing PSII centers in F. cylindrus provides the cell with protection against photoinhibition by facilitating the rapid induction of NPQ. This strategy provides an important ecological advantage, especially during the Antarctic spring, maintaining photosynthetic efficiency under high light and nutrient-limiting conditions. © 2011 Phycological Society of America.